2017
DOI: 10.1186/s12941-017-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lytic bacteriophages for control of multidrug-resistant Salmonella Typhimurium

Abstract: BackgroundThe emergence of antibiotic-resistant bacteria can cause serious clinical and public health problems. This study describes the possibility of using bacteriophages as an alternative agent to control multidrug-resistant Salmonella Typhimurium.MethodsThe potential lytic bacteriophages (P22-B1, P22, PBST10, PBST13, PBST32, and PBST 35) were characterized by morphological property, heat and pH stability, optimum multiplicity of infection (MOI), and lytic activity against S. Typhimurium KCCM 40253, S. Typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
(28 reference statements)
6
17
0
Order By: Relevance
“…The effect of pH on phage viability at 25℃ and at 40℃ represented activity at room temperature and body temperature of chicken, respectively. The two phages were tolerant to a broad range of pH similar to what was observed in previous studies [26]. The tolerance to a broad range of temperature and pH coupled with a wide host range, makes the two phages suitable potential candidates for a cocktail product that can be used as an alternative to antibiotics in the control of APEC infections [27].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The effect of pH on phage viability at 25℃ and at 40℃ represented activity at room temperature and body temperature of chicken, respectively. The two phages were tolerant to a broad range of pH similar to what was observed in previous studies [26]. The tolerance to a broad range of temperature and pH coupled with a wide host range, makes the two phages suitable potential candidates for a cocktail product that can be used as an alternative to antibiotics in the control of APEC infections [27].…”
Section: Discussionsupporting
confidence: 78%
“…pH stability and thermal stability tests were carried out for the two phages with the broadest host ranges as described by Jung et al and Yu et al [26,27]. Briefly, the phages (10 8 PFU/ml) were incubated at different temperatures (20℃ to 70℃ ) for 30 mins.…”
Section: Ph and Thermal Stability Testmentioning
confidence: 99%
“… Brackett et al (1997) demonstrated that a synthetic peptide corresponding to amino acid residues 20 through 44 of the neutrophil-derived 37-kDa cationic antimicrobial protein (CAP37 P20–44) can bind lipid A of LPS, which could be useful in attenuating in vivo responses induced during endotoxemia, including sepsis. The emergence of antibiotic-resistant bacteria can cause serious clinical and public health problems ( Jung et al, 2017 ). N4-like phages have been used as therapeutic agent in phage therapy against Pseudomonas aeruginosa infections and have been shown to be safe and effective ( Shigehisa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, phage clearance is also enhanced by the mammalian innate immune responses to infection — this may affect (or be affected by) amplification and/or phage dosage (the ratio of phages to bacteria; ie, the MOI). An MOI below 0.1 is effective in mouse models, but an optimal MOI to use in humans has been suggested to be ten or over . Bacterial concentrations are 10 1 –10 5 (more usually < 10 3 ) colony‐forming units per mL of blood in severe sepsis, and thus a dose of 10 9 plaque‐forming units (PFU) into the human blood volume (~ 5 L) is expected to yield an MOI input over 200.…”
Section: Phage Dosing and Kinetics: Pharmacokinetics Pharmacodynamicmentioning
confidence: 99%
“…An MOI below 0.1 is effective in mouse models, 47 but an optimal MOI to use in humans has been suggested to be ten or over. 48 Bacterial concentrations are 10 1 -10 5 (more usually < 10 3 ) colony-forming units per mL of blood in severe sepsis, 49 and thus a dose of 10 9 plaque-forming units (PFU) into the human blood volume (~ 5 L) is expected to yield an MOI input over 200.…”
Section: Phage Dosing and Kinetics: Pharmacokinetics Pharmacodynamicmentioning
confidence: 99%